Modeling public attention behavior on badminton’s ecosystem evolution via complex network theory - Liang, Yongjie; Xu, Yuan; Gu, Runsheng; Hu, Jun; Li, Huijia (Frontiers in Sports and Active Living, 2025)
The growing convenience of badminton and the expansion of related venues have increased the complexity of public attention toward the sport, making nonlinear research methods an effective approach for exploring the evolutionary dynamics of its popularity. The visibility graph algorithm was adopted to characterize badminton search volume as a dynamic behavioral indicator of the badminton attention complex system, enabling systematic investigation of the system's evolutionary process and dynamical characteristics. Results show that the evolutionary process of the badminton attention complex system exhibits small-world and approximately scale-free network properties, coupled with chaotic dynamical behavior characteristics. This indicates that the badminton attention complex system is ultimately a deterministic nonlinear dynamical system governed by chaotic dynamics.